Evaluation of the Implementation of the Inclusion Program at the State Elementary School 01 Sungai Bambu, North Jakarta - Rokhim, Abdul; Suryadi, Suryadi; Supadi, Supadi (International Journal of Elementary Education, 2021)
This study aims to describe the context, input, process, and product of the Inclusive Education program. This research is a program evaluation research using the CIPP model. The methodology used is a survey and descriptive method. The study was conducted at the State Elementary School 01 Sungai Bambu, North Jakarta. The research informants were the Principal, vice-principal of the curriculum and student affairs department, Mr and Mrs teachers, special assistant teachers. Data collection techniques through observation, questionnaires, and interviews. Based on data analysis, the main obstacle to inclusive education programs experienced by schools was the presence of non-permanent accompanying teachers, who only received one per week, thus hampering the development of students with special needs. In addition, the facilities and infrastructure that support the learning process are incomplete. The unique curriculum for inclusive education at SD N 01 Rawa Bambu needs to be re-examined to improve learning abilities for children with special needs.